Exploring Collaboration Between Midwives and Nurses in Nova Scotia: A Feminist Poststructuralist Case Study - Macdonald, Danielle (Université d'Ottawa / University of Ottawa, 2019)
Background: In 2009, midwifery became a regulated profession and was integrated into the delivery of perinatal health care in Nova Scotia at three model sites. The integration process was challenging for health care providers, and particularly for midwives and nurses, who have different scopes of practice, yet similar roles and skills. Little is known about how midwives and nurses collaborate. Purpose: The purpose of this study was to explore collaboration between midwives and nurses in Nova Scotia, Canada. Methodology: This research was conducted as an instrumental case study, guided by Stake's approach for qualitative case study research. Intersectional feminist poststructuralism (IFPS) provided the theoretical perspective to explore concepts of; power, discourse, and gender, as they related to collaboration between midwives and nurses. Individual, one on one interviews with 17 participants were audio-recorded and transcribed verbatim. Twenty-five documents were reviewed, and field notes were maintained. Feminist poststructuralist discourse analysis was used to analyze the data. Findings: Four main themes were identified; 1) Negotiating Roles and Practices: ‘Every Nurse is Different, Every Midwife is Different, Every Birth is Different’, 2) Sustaining relationships: ‘The more we can just build relationships with one another’, 3) Reconciling Systemic Tensions: The Medical Model and the Midwifery Model, 4) Moving forward: A Modern Model for Nurses and Midwives Working Together. Discussion and Implications: This study illustrated the potential for building more collaborative teams of midwives and nurses in Nova Scotia, and in Canada. Midwives and nurses in Nova Scotia are positioned to demonstrate leadership in a midwife and nurse led birthing model of care that works. More research, leadership, government funding and support is needed to implement this model of care. Conclusion: The findings of this study can be used to build sustainable, collaborative, equitably distributed midwifery (and birthing) services in Nova Scotia, and throughout Canada.
Keywords: Midwifery; Nursing; Collaboration; Feminism; Case Study